MORPHOLOGICAL AND PHYSIOLOGICAL PECULIARITIES OF DIFFERENT BREED BOARS’ SPERMATOZOA UNDER THE ACTION OF HEAT STRESS - Pavlova, I. V. (Scientific Progress & Innovations, 2020)
In summer, farm animals are subjected to intensive heat stress, which is accompanied by a decrease in their reproductive function, especially with significant temperature fluctuations. It has been found out that at high temperatures the quality of sperm deteriorates significantly, especially with regard to survival, total sperm count, morphometric parameters, and the number of defective forms. The aim of the research was to determine the influence of humic substances on morphological and physiological indexes of breeding boars’ sperm during heat stress. Adult breeding boars of two breeds, Poltava Meat (PM) and Red-White-Belted meat (RWB) breeds, analogues by age, live weight and quality of sperm, were used in the experiment. The animals were fed with biologically active feed additive “Humilid” during heat stress. As a result of the study it was found that the development of heat stress during the month deteriorated the quality of sperm production in breeding boars and reduced ejaculate weight, sperm count and motility in Poltava Meat breed, by 23.7 %, 21.9 % and 14.6 %, , and in Red - White -Belted meat breed – by 28.4 %, 17.6 % and 22.9 %, respectively. On the 30th day of the experiment, under the action of heat stress, the morphometric indexes of spermatozoa in the breeding boars’ ejaculates changed: the total length decreased in Poltava Meat breed by 2.3% (p<0.01) and in Red-White-Belted meat breed by 2.6 %; head length decreased by 30. 2% (p<0.001) and 5.4 % (p<0.001,) respectively. In animals of the control group of Poltava Meat breed under the action of thermal factor, a larger number of pathological spermatozoa forms was detected on the 30th day – 17.1% and on the 60th day of the experiment, they reduced by 4.5 %. While in Red-White-Belted meat breed, abnormal spermatozoa forms had a more significant tendency to increase by 54.8 % and 34.2 %, respectively. Feeding humates to breeding boars improved the adaptability of Poltava Meat breed as to increasing the spermatozoa concentration at the end of the main period by 13.8 % and survival ability by 11.5 %, respectively, whereas in animals of Red-White-Belted meat breed, only an increase in spermatozoa concentration by 14.7 % was observed. The using of humates for 60 days resulted in increasing the adaptability to heat stress and also increasing spermatozoa length by 7.3 % in Poltava Meat breed and by 9.7 % in Red-White- Belted meat breed together with decreasing the number of pathological forms.